2013
DOI: 10.4236/aasoci.2013.33023
|View full text |Cite
|
Sign up to set email alerts
|

Providing Sustainable Supports for Street Children in Nigeria:Stakeholders Challenges and the Policy Options Available

Abstract: This article examines the limitations of all stakeholders in providing support for street children in Nigeria in the face of continuous increase in their number with a view to identify possible policy options in the light of inabilities of the stakeholders to adequately support the children. Qualitative research techniques were employed to collect the primary data from NGOs, community members and government agencies saddled with the responsibility of caring for the children. It was found that the stakeholders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…Children from such families as mentioned above always have difficulties to feed as some days may go by without them having any food in the house for them and their siblings thereby pushing some of them to embark on the option of running into the streets to look for opportunities to make money to support their families. This also helps to explain why some of the respondents began involving into street life while still at home since they were looking for things/jobs to do on the street to make money to be able to financially support their families just as similar patterns among street children have been reported in other studies as they concur with this results [4,6,7,9,13,14].…”
Section: Family Profile/family Socio-economic Statussupporting
confidence: 85%
See 2 more Smart Citations
“…Children from such families as mentioned above always have difficulties to feed as some days may go by without them having any food in the house for them and their siblings thereby pushing some of them to embark on the option of running into the streets to look for opportunities to make money to support their families. This also helps to explain why some of the respondents began involving into street life while still at home since they were looking for things/jobs to do on the street to make money to be able to financially support their families just as similar patterns among street children have been reported in other studies as they concur with this results [4,6,7,9,13,14].…”
Section: Family Profile/family Socio-economic Statussupporting
confidence: 85%
“…The majority of street children have parents who are less educated, abused substances, while others come from polygamous families (In the current study, slightly more than half of the respondents 50.9% came from polygamous homes), with parents having only manageable sources of income leading to poor economic status and making it difficult for their parents to provide them with basic needs [13,14].…”
Section: Family Profile/family Socio-economic Statusmentioning
confidence: 61%
See 1 more Smart Citation
“…Lastly, the implication of the results of the hypotheses testing carried out on all seven hypotheses was that improvement of the staffing, communication, alliance-building, earnings-generation, replication and stimulating market forces capabilities of youth-serving NGOs will be beneficial in the replication of successful programmes designed to empower poor youths. As result of this implication, youth-serving NGOs should endeavour to resolve their -staffing (Aransiola, 2013;Odukoya, Busari, & Ateh-Abang, 2006); communication (Nwogu, 2014); alliance-building (Kasali et al, 2015); lobbying (Momoh et al, 2015). Earnings-generation (Aransiola, 2013;Oyelude & Bamigbola, 2013); replication (Adepoju & Oyesanya, 2014;Nwogu, 2014;Patrick & Ijah, 2012;Samuels, Blake & Akinrimisi, 2012); and stimulating market forces challenges (Akpan et al, 2015) in time in order to achieve their youth poverty alleviation goals in society.…”
Section: Pearson's Correlation R Resultsmentioning
confidence: 99%
“…It is important to add that previous studies on the activities of youth-serving NGOs in Nigeria have revealed that, in their attempt to alleviate youth poverty in Nigeria, youth-serving NGOs have several organisational capability challenges with regard to -staffing (Aransiola, 2013;Iwuchukwu, Nwankwo, & Igbokwe, 2014); communication (Nwogu, 2014); alliance-building (Kasali, Ahmad, & Ean, 2015); lobbying (Momoh, Oluwasanu, Oduola, Delano, & Ladipo,2015); earnings-generation (Aransiola, 2013;Oyelude, & Bamigbola, 2013); replication (Adepoju & Oyesanya, 2014;Mac-Ikemenjima, 2005;Ohize & Adamu, 2009); and stimulating market forces (Akpan, Patrick, James, & Agom, 2015). Furthermore, organisational capability challenges may hinder the capacities of youth-serving NGOs to replicate successful programmes designed to empower poor youths in Nigeria and to fight youth poverty in Nigeria, as evidence from various studies show certain problems that negatively affect the fight to alleviate youth poverty in Nigeria by youth-serving NGOs, namely: inadequate staffing (Aransiola, 2013); insufficient funding (Nwogu, 2014); poor communication (Nwogu, 2014); reduced support from development partners (Kasali et al, 2015); and a lack of capacity to negotiate with government (Momoh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%